A study in the theory of open inflation - Paunio, J.J. (Finland Bank of Finland Institute of Economic Research, 1961)
This study approaches its subject matter from the angle of some generally held views on the tasks and possibilities of economics, and in particular, economic theory.
Includes bibliographical references
osc 18/01/2019
Loans
Keywords: Inflation